CEO Education, Financial Decision and Firm Performance - Rahmat Setiawan; Lila Gestanti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2018)
Many previous studies have shown that the number of CEOs holds MBA is still low and less dominating. We analyze the effect of CEOs with MBA degree on funding decision, investment decision and firm performance. Using 38 manufacturing companies that listed on Indonesia stock exchange during 2010-2017 analyzed with multiple linear regression. We find that CEOs with MBA degree significantly have lower interest-bearing debt, higher capital expenditure and higher return on asset than companies with non-MBA CEOs. These research results provide information to shareholders and management of manufacturing companies to consider and provide equal opportunities to hire MM-MBA CEOs.